Larson Powell. The Technological Unconscious in German Modernist Literature: Nature in Rilke, Benn, Brecht, and Döblin. Rochester: Camden House, 2008. 256 pp. - Christa Spreizer (Studies in 20th & 21st Century Literature, 2014)
Review of Larson Powell. The Technological Unconscious in German Modernist Literature: Nature in Rilke, Benn, Brecht, and Döblin. Rochester: Camden House, 2008. 256 pp.
Keywords: German literature; modernism; nature